Analytical study of the Kalman filter for stationary dynamic systems - Bidyuk, Petro; Podladchikov, Vladimir; Podladchikova, Iryna (Zielona Góra: Uniwersytet Zielonogórski)
This paper is devoted to development of analytical approach to the Kalman filter study. This approach is based upon making use of Riccati equation solution for a class of dynamic systems considered, as well as Kalman and Wiener filters transition matrices. An example of a moving object state estimation shows advantages of the method proposed, the main of which are substantial reduction of computational expenses on modelling of estimation algorithm and a possibility of analytical study of estimation results. A case of correlated measurement noise is also considered.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka